THE DUAL ROLE OF DIRECT SELLING AGENTS: BALANCING BANK AND CUSTOMER NEEDS IN HOME LOAN SERVICES IN PUNJAB - Devi, Priya; Dwivedi, Aanchal; Mahajan, Shivani (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Purpose The purpose of this study is to investigate the dual function of Direct Selling Agents in the home loan industry of Punjab, India. It examines how these intermediaries navigate the competing objectives of financial institutions. Design/methodology/approach the research employs a mixed-methods, sequential explanatory design. Quantitative data was gathered through structured surveys from 392 DSA (87% response rate). This was followed by a qualitative phase involving semi-structured interviews with 20 DSA, 10 bank officials, and 15 home loan customers to explore operational realities and ethical challenges. Findings reveal that while improve loan processing speed (78.3%), they operate in high-pressure environments characterized by conflicting interests. The top challenge identified is meeting sales targets while ensuring customer suitability. Results indicate that building trust and maintaining transparency are primary strategies for success, though navigating ethical dilemmas remains the most difficult aspect of the role. Originality This paper contributes to the limited body of research on the socio-economic effects of financial intermediaries in the Indian housing market. It shifts the focus from simple sales figures to the quality and ethical standards of financial intermediation in regional emerging markets like Punjab. Research limitations/implications the study’s geographical focus on Punjab may limit the generalizability of the findings to the entirety of India. Practical implications the study provides a roadmap for banks to refine management policies by implementing more stringent ethical oversight and balanced performance metrics that consider customer satisfaction alongside sales targets.